Methodological challenges in assessing the viability of agroecological practices: lessons from a multi-case study in Africa - Andrieu, N.; Dedieu, B.; Girard, P.; Scopel, E.; Magaju, C.; Dembele, C.; Mekuria, Wolde; Coe, R. (Springer, 2025)
Despite a growing literature highlighting the benefits of agroecology in Africa, policy makers, donors, and scientists are still debating the “viability” of agroecological practices. However, assessing the viability of agroecological practices poses challenges, and so far, no studies have clearly documented them and options for addressing them. The aim of this paper is to describe the main methodological challenges we faced in assessing the viability of agroecology in 11 case studies in Africa so that others planning assessments can benefit from what we learned. Seven methodological challenges discussed are (i) defining an object of study through a list of practices or agroecological principles, (ii) having a practice-based assessment versus a systemic assessment at field or farm scales, (iii) having a subjective assessment of the viability of agroecological practices based on farmers’ perspective or an “objective” assessment, (iv) having a qualitative or quantitative assessment, (v) having a diachronic versus synchronic assessment, (vi) having a multisite approach versus a single-site study, and (vii) having a context-specific assessment method or a unitary assessment method. We conclude that the assessment of the viability of agroecological practices needs to be multicriteria, systemic, and based on farmers’ perspectives and not practice-based using a single simple metric. This is a change from the conventional way such systems are evaluated based on quantitative metrics. We recommend using a mixture of quantitative and qualitative assessments that highlight farmers’ perceptions of practices embedded into their farming systems, using transversal and context-specific data.